The Role of Participatory Communication in Motivational Interviewing in Handling Drug Abusers (Case Study of Clients in the Mild and Moderate Categories at the BNN Primary Clinic in South Kalimantan Province) - Muzahid Akbar Hayat; Decky C. Kananto Lihu; Rakhmadiansyah Rakhmadiansyah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Drug abuse is a complex problem that impacts health, social, and economic aspects. Rehabilitation efforts are crucial in addressing it, particularly through an effective and humanistic communication approach. This study aims to explore the role of participatory communication in the Motivational Interviewing (MI) method in the rehabilitation process for mild and moderate drug abusers at the Pratama Clinic of the National Narcotics Agency (BNN) in South Kalimantan Province. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and documentation with six clients and one counselor. The results indicate that participatory communication plays a crucial role in building an equal, empathetic, and inclusive counseling relationship. Clients feel more valued, heard, and encouraged to be active in the recovery process. However, challenges remain, such as differences in socio-cultural backgrounds and client passivity. In conclusion, participatory communication supports the effectiveness of MI in increasing client motivation and engagement, and is an important strategy in creating a more humane and sustainable rehabilitation process.